EVALUASI PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) DI PROVINSI JAWA TENGAH - Haryono Haryono; Ahmad Syaifudin; Sri Widiastuti (Universitas Negeri Semarang, 2015)
This study aimed to evaluate the components management of the inclusive education implementation in Central Java province. This study was designed with model of CIPP (Context, Input, Process, and Product). Subjects of the study include teachers, parents, principals, school committees, and the Department of Education and Culture. Instruments used to obtain the data in this study were varied according to the revealed variable. The research instruments used include questionnaires, observation guides, interview, and documentation. The findings of this study revealed that through an instrument system of accreditation inclusive education, the management of inclusive education component in Central Java province generally rated category C (total score = 24-43) and was not even accredited (total score = 24). Meanwhile, school accreditation of SLB in Central Java generally rated category B (total score of 44-63).Keywords : ABK, inclusive education